PENELANTARAN ORANG TUA DALAM LINGKUP RUMAH TANGGA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA: PENELANTARAN ORANG TUA DALAM LINGKUP RUMAH TANGGA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Wardah Nuroniyah (Pusat Studi Gender dan Anak Universitas Islam Negeri (UIN) Mataram, 2019)
Abstract One of the acts of domestic violence against people in the household sphere is neglect. Parental neglect is negligence of the child towards the biological mother's father who has a dependency in physical needs (negligence to provide adequate food, clothing, or hygiene), and emotional (negligence to provide care or affection). neglect of parents is included in the form of lawlessness to parents because parents have rights to their children. So that for each perpetrator of neglect parents must be subject to sanctions. This study aims to answer the questions that formulate the problem: